Sources of output growth in the countries of the Common Monetary Area and the provinces of South Africa - Dukhabandhu Sahoo; Auro Kumar Sahoo; Jayanti Behera; Diptimayee Mishra; Phendulwa Zikhona Makunga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper aims to decompose the sources of growth in economies in the Southern African region's Common Monetary Area and in the provinces of South Africa. Decomposition results for the Common Monetary Area reveal that the growth of aggregate and sectoral gross domestic product is driven by input, without increasing efficiency in production or benefiting from technological progress, which is unsustainable. Negative technical change implies that countries are unable to reap the benefits from shifts in technology. Countries experiencing input-driven growth in the secondary sector, such as Namibia and Eswatini, have the potential to achieve growth through efficiency improvements and by adopting technology. Output growth in the provinces of South Africa is negatively contributed by changes in technical efficiency, which suggests that policy makers should raise growth further by emphasizing improvements in efficiency in these provinces.
Keywords: C23; O33; O47; O55; 330; growth; efficiency; technology; Southern African region; decomposition